INTEGRATING GENOMICS INTO DENTISTRY: BUILDING KNOWLEDGE, SHAPING PERSPECTIVES, AND ENHANCING PRACTICES - Priyadarshi, Dr Surbhi; Ms. Aditi; Ms. Manasvi; Srivastava, Dr. Rangoli; Kumar, Dr. Shweta; Kumar, Ashutosh (Journal of Neonatal Surgery, 2025)
Aim: To assess the knowledge, attitudes, and practices regarding genomics in dentistry among dental professionals in India. Materials and Methodology: A descriptive cross-sectional survey was conducted with 400 dental professionals, including undergraduates, postgraduates, academicians, and private practitioners. Data were collected using a structured online questionnaire covering demographics, knowledge, attitudes, and practices related to genomics. Statistical analysis, including chi-square tests and logistic regression, was performed to identify associations between demographic factors and survey responses. Results: The study revealed significant variations in awareness of genomics across different educational qualifications. The most knowledgeable individuals were undergraduate dental students, especially when it came to the Human Genome Project and genetics in preventative care. Just 61.3% of respondents were aware of genomics' use in diagnostics, but 93% of respondents acknowledged its potential in preventative dentistry. With 76.5% of respondents supporting genetic counselling services, the majority favoured incorporating genomic knowledge into dental practice and education. The lack of testing facilities (41.25%), cultural reasons like religious views (17%), and financial limitations (23%), were the main obstacles. Conclusion: The study highlights a positive perception of genomics among dental professionals but identifies significant gaps in knowledge and application, particularly among private practitioners. Targeted efforts to incorporate genomics into dental curricula, along with professional development programs, are essential to bridge these gaps and enhance the integration of genomics into dental practice.